Analisis Kelembagaan dalam Monitoring Kualitas Air Sungai Ciliwung di Wilayah Provinsi DKI Jakarta - Aflakhur Ridlo (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2017)
Institutional research and policy analysis of water quality monitoring of the Ciliwung River has been conducted since the year 2015. This activity is the result of cooperation between the Ministry of Environment and Forestry of Indonesia and the Agency for Assessment and Application of Technology. Due to the complexity of the Ciliwung River flows and water quality problem that passed the administrative authority of DKI Jakarta, the methodology of this study was emphasized in depth interviews to stakeholders in the management of the Ciliwung River. The plan to install some online system of river water quality monitoring is expected to run well and in accordance with existing laws and regulations. In addition, the readiness of the operationalization of this monitoring system to run well. Institutional strengthening forms and open method of coordination can be adopted to reduce communication and coordination barriers that are rigid and Weberian. From this study it is concluded that Jakarta Environmental Management Agency is the strongest candidate as one of the managers of online monitoring system of Ciliwung river water quality. Institutionally public intervention on river management in general can suppress water quality pollution which can threat n the health of people living around Jakarta area. Online Mortitoring system can be utilized by preparing a reliable institutional arrangements